O svetlobnem tlaku - Strnad, Janez (Obzornik za matematiko in fiziko, 2012)
The radiation pressure is bound to the momentum of light. The connection of momentum with the energy of light may be used in high school as a point of departure for the approach to quantum mechanics. In the article the background of the classical equation is discussed. Phenomena are described forw hich the radiation pressure is decisive. The equation for the radiation pressure is derived in a simple way. Objections against the derivation of the equation are mentioned. Remarks are added which may be useful for teachers.
Keywords: fizika; gibalna količina; sevalni tlak; svetloba